Synthesis of I@MPA-Mn:ZnSe as an efficient contrast agent for CT/ fluorescence bi-modal imaging application - Alhasan, Ammar; Sani, S.F. A.; Tajuddin, Hairul Anuar; Ali, Tammar Hussein; Hisham, Shameer; Ung, N.M.; Azhar, Nurul Amniyyah; Said, Nur Akmarina BM; Jamil, Amira Hajirah Abd; Bradley, D.A. * (Elsevier, 2023)
Bi-modal imaging contrast agent has attracted considerable attention in medical physics research field via quantum dots (QDs) fabrications. Doped quantum dots are playing an important role in seeking alternatives to conventional heavy metal-containing particles for medical applications. In order to improve imaging diagnosis, herein we report the design and synthesis of I@MPA-Mn:ZnSe as an efficient contrast agent. The medium, mercaptopropionic acid (MPA) capped Mn:ZnSe QDs surface-conjugated with a commercial contrast agent (Iohexol), was synthesized in seeking to overcome the limitations of Iohexol, also towards advancing bi-modal imaging approaches. In this study, morphology, elemental, absorption and fluorescence analysis were investigated, followed by a preliminary study of CT contrast enhancement and cell viability. In comparison to Iohexol, the fluorescence of I@MPA-Mn:ZnSe is observed at 585 nm. The CT Hounsfield unit (HU) increases linearly with mass concentration, with a four-fold increment in HU over that of Iohexol, producing greater than 328 ΔHU at similar concentrations, confirming the CT contrast efficiency of I@MPA-Mn:ZnSe. Cytotoxicity studies have confirmed that the medium possesses good biocompatibility and low toxicity to cells (HepG2 and MDA-MB-321). Present results for CT enhancement and brightness of fluorescence of I@MPA-Mn:ZnSe point to its great potential as a bi-modal contrast medium for further diagnosis applications.